Microstructure and mechanical properties of refractory MoNbHfZrTi high-entropy alloy - Guo, N.N.; Wang, L.; Luo, L.S.; Li, X.Z.; Su, Y.Q.; Guo, J.J.; Fu, H.Z. (Materials in engineering, 2015)
[Display omitted] •A new refractory MoNbHfZrTi high-entropy alloy with single BCC phase is prepared.•The single disordered BCC phase has high structural stability.•The compressive yield strength is 1719MPa at room temperature.•This alloy still has high compression yield strength at elevated temperatures.•The dynamic recrystallization occurs during elevated-temperature compression. The present paper reports the microstructure, phase stability and mechanical properties of a new refractory MoNbHfZrTi high-entropy alloy. MoNbHfZrTi alloy consists of a disordered body-centered cubic (BCC) solid solution phase in as-cast and homogenized states. Homogenization treatment and DSC analysis indicate that there is no any phase transition below 1743K. At room temperature, the compressive yield strength for the alloy in as-cast and as-homogenized states reaches about 1719MPa and 1575MPa, respectively and the fracture mechanism is brittle quasi-cleavage fracture. At elevated temperatures, this alloy has compression yield strength of 825MPa at 1073K, 728MPa at 1173K, 635MPa at 1273K, 397MPa at 1373K and 187MPa at 1473K and some fine grains form at grain boundaries due to partial dynamic recrystallization.